(3GdPNjQIs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3GdJGSY ai CeQGV GdCPf GdYGTQ ai CeQGV GdCfa , GdMGOi YTQ ai CeQGV Gdae hajg YdGL GdfMQ hGddgGI hGdNhGfjb s
(3BNQgG (B:s
(3GdQchH hEOeGf GdMeGe hGdJYQb ajg, bGd GdMGQK Hf cdOI ef CQGO CdGjMHd adjOgf MTaJg Yf GdLeGY s
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B96 s
Keywords: (3GdWHs